A Hybrid Systematic Review and Meta-Analysis of Management Practices in Philippine Higher Education Institutions - Shalima Sappayani; Naf’an Tarihoran; Farid Mahruf; Ilzamudin Ma'mur (Jurnal Educative: Journal of Educational Studies, 2025)
This study employed a hybrid systematic review and meta-analysis to examine the impact of management practices on institutional outcomes in Philippine higher education institutions (HEIs) from 2019 to 2023, with an updated search extending to 2025. A total of 32 peer-reviewed studies were included in the qualitative synthesis, while 11 met the criteria for empirical inclusion; however, only six provided sufficient statistical data and were included in the meta-analysis. The meta-analysis yielded a moderate and statistically significant pooled effect size (Cohen’s d = 0.516, 95% CI [0.452, 0.581]), indicating that management practices—particularly in the areas of resource allocation, curriculum implementation, and strategic planning—positively influence accreditation performance, instructional quality, and digital readiness. Substantial heterogeneity (I² = 89.6%) indicates considerable variation across institutional types, regions, and management domains. A thematic synthesis of qualitative studies further identified recurring patterns in related to adaptive leadership, quality assurance, and digital transformation. By integrating quantitative and qualitative evidence, this study advances current understanding of effective management approaches in Philippine HEIs and highlights the importance for context-responsive, resilient, and data-driven leadership frameworks. The findings offer practical implications for academic leaders, administrators, and policymakers seeking to strengthen institutional performance and governance in a rapidly evolving higher education landscape.